Applying the fraud triangle theory to examine fraudulent cases from the perspective of working adult - Lau, Alex Chin Yeh (2024)
In today’s world, fraud poses a significant threat to individuals, organizations, and economies worldwide, with devastating consequences ranging from financial losses to reputational damage and legal repercussions. This research aims to explore the factors that influence the fraudulent behavior from the perspective of working adults, focusing on the fraud triangle theory, which includes pressure, opportunity, and rationalization. For the research methodology, this study will employ the quantitative research design, and leveraging the convenient sampling methods which is good in quick data collection. Through surveys and data analysis of responses from 250 working adults, this research will be able to investigate the relationships between pressure, opportunity, rationalization, and fraudulent cases in working adult’s perspective, providing insights into the dynamics of fraudulent behavior in professional contexts. The result of the data analysis had proved that both pressure, opportunity, and rationalization have relationships with fraud cases in working adult perspective. The findings of this research will offer valuable insights for academia, industry professionals, and decision-makers, providing a deeper understanding of fraud dynamics and informing the development of targeted prevention strategies and organizational policies. For example, Implications include aiding government policy formulation by addressing financial pressures and protecting whistleblowers, enhancing organizational risk management through tailored prevention strategies and improved internal controls, implementing training programs to raise awareness and foster ethical behavior, and promoting a culture of integrity within organizations to mitigate fraud risks and enhance reputation. Besides the implications, the limitations of this research and the recommendation for the future research will also be discussed in the report. In conclusion, this study contributes to bridging the gap between theory and practice in fraud prevention, fostering a culture of transparency, integrity, and ethical behavior in the workplace.